The Effect Of Potato Starch Substitution On The Quality Of Skippy Cookies - Eka Wati, Maisa Siska; Gusnita, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research is motivated is  the lack of variation in the use of potato starch in food processing.The main ingredient inmaking skippy cookies is wheat flour which is still imported. Potato flour has a fairly complete nutritional value, in addition to the low gluten content in potato flour, it is possible to use it as a substitute for wheat flour with low protein content. This study aims to analyze the quality (shape, color, aroma, texture and taste) of skippy cookies substituted with potato flour as much as 0%, 20%, 40% and 60%. This type of research is a pure experiment using the Completely Randomized Design (CRD) method. The data used are primary data obtained directly from 3 expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of potato flour skippy cookies. The data that has been obtained is then tabulated in the form of a table and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount ≥ Ftable, then it is continued with Duncan's test. The results showed that the substitution of potato flour had an effect on the quality of the texture and taste of the beans, while those that had no significant effect were round shape, neat shape, color, aroma and sweet taste. The result of the best quality test of skippy cookies with potato flour was in the X1 treatment with 20% potato starch substitution.